2017
DOI: 10.1021/acs.energyfuels.6b02421
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Near-Infrared (NIR) Spectroscopy and Principal Component Analysis (PCA) To Discriminate Bark and Wood of the Most Common Species of the Pellet Sector

Abstract: The pellet energy market is expanding rapidly in Europe and also at the global level, in response to the continuously growing energy demand and because of the high degree of reliability, the easy handling, and the cheap and simple logistics, in comparison to other solid biomasses. The fast growth of this market has highlighted the problem of product quality, which has strong repercussions for technical, environmental, and economic aspects. The biomass quality is defined by several chemical–physical parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…This is probably due to the fact that biomass producers use intermediate storage-generally uncovered-to create a buffer of feedstock, securing the provision to the end user in adverse weather conditions. This is confirmed by several studies on the effect of storage of wood chips [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], which leads to variations of the fuel properties, particularly if prolonged for several months. Additionally, wood chips from different forest operations are delivered and mixed at the intermediate storage, thus including several species and diverse tree sections.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This is probably due to the fact that biomass producers use intermediate storage-generally uncovered-to create a buffer of feedstock, securing the provision to the end user in adverse weather conditions. This is confirmed by several studies on the effect of storage of wood chips [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], which leads to variations of the fuel properties, particularly if prolonged for several months. Additionally, wood chips from different forest operations are delivered and mixed at the intermediate storage, thus including several species and diverse tree sections.…”
Section: Discussionsupporting
confidence: 65%
“…Nystrom and Dahlquist [23] compared several alternative technologies with the standard oven dry method, concluding that Near Infrared (NIR) spectroscopy and Radio Frequency (RF, also known as dielectric) technologies were the best-suited for MC measurement in flow and bulk fuels, respectively. More recently, further studies confirmed the potential of NIR instruments for MC determination due to their real-time and intuitive approach and the possibility to measure samples without any specific preparation or alteration of the biomass [24], allowing reiterate analysis on the same sample, if required. However, fuel-specific calibration is necessary for correct NIR deployment, making it a less flexible option in conditions of high variability of the biomass characteristics [19].…”
Section: Introductionmentioning
confidence: 83%
“…In this work we tentatively assigned this band to lignin because it appears in the lignin Klason spectra from the same samples (not shown). Toscano et al. (2017) already highlighted this peak as one of the most relevant wavelengths for the discrimination between bark and wood samples.…”
Section: Resultsmentioning
confidence: 93%
“…When infrared energy falls on the surface of wood samples, the energy of the C-H, N-H, and O-H bonds is excited above their ground state and, depending on inner structure, composition, and surface feature, the Vis-NIR spectra can be translated into fiber morphology and chemistry information through multivariate modeling and removal of noise and irrelevant information [19,20]. Therefore, advanced spectral optimizing techniques should be explored to extract key information and improve model performance.…”
Section: Introductionmentioning
confidence: 99%